Lim Boon Keng : the musical - Stella Kon @ Lim Sing Po (2017)
This submission contains the Libretto of the work entitled “Lim Boon Keng The Musical” and the Exegesis thereof. The Libretto was composed during the period of writing this thesis. Music for the songs was written by Composer Desmond Moey, and lead sheet scores for four of these songs are attached. Exegesis of the musical includes themes and ideas that were taken into consideration in writing the Libretto, and an account of its development over the past twenty years. An Appendix includes previous versions of the Libretto since 1994.